Longer Life and Higher Fertility in an OLG Economy with Production. (5th November 2013) - Fanti, Luciano
Abstract : This paper investigates the effect of a change in life expectancy (i.e., longevity) on fertility in a standard OLG economy. The main result is that, in contrast with other papers, an increase in the longevity rate may increase the fertility rate as well. It is shown that such a result holds when the cost of rearing children in terms of goods and services (rather than in terms of forgone wages) matters. In particular, such a result depends on the relative "strength" of the capital in the technology as compared with the "strength" of the parsimony. Moreover it is shown, again in contrast with other papers, that with an unfunded social security system it is more likely that a longer life may increase the fertility. The latter result is even more likely in the presence of child subsidy policies, which are widespread in developed countries. In conclusion, we argue that in countries having a population with a high longevity, a high capital share, a large unfunded social security, and child subsidy policies (such as Italy), a further increase of longevity may increase fertility in the long run and thus partially alleviate the peril of the so-called "demographic bomb."